(3TQM QSGdI RjJhf GdcHjQs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3RjJhf GdcHjQ JdejP GQSWGWGdjS hddTjN GdjhfGfi QSGFd bO TQMgG GdfUGQi TQhMkG JQchG HYVgG hRGO h ajgG s
(3BNQgG (B:s
(3hef cGf HNdGa Pdc agh Mcje egQL fYhP HGddg ef YPGH GdBNQI Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQg eY GdeNWhW Qbe (B110 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B- (3cdjI GdMbhb (B(112 - (3H(B) s
Keywords: (3GdadSaI hGdefWbs